Generation of monoclonal antibodies specific to ribosomal protein S6 kinase 1 - Savinska, L.O.; Klipa, O.M.; Demchuk, N.O.; Ovcharenko, G.V.; Malanchuk, O.M.; Tykhonkova, I.O.; Palchevskyy, S.S.; Filonenko, V.V. (Вiopolymers and Cell, 2012)
The aim of this study was to produce monoclonal antibodies directed to the N-terminal regulatory region of S6K1,
which shows very low homology to S6K2. Methods. Hybridoma technology, ELISA, Western blot, Immunoprecipitation. Results. Three hybridoma clones (A1, A2 and A3) producing mAbs specific to ribosomal protein S6
kinase 1 have been generated. Specificity of mAbs has been confirmed by Western blot and immunoprecipitation
technique. Conclusions. The obtained antibodies are suitable for elucidating signal transduction pathways
involving S6K1.
Keywords: ribosomal protein S6 kinase, mAbs. Мета. Отримати моноклональні антитіла проти N-кінцевої регуляторної ділянки кінази рибосомного білка S6-S6K1, який має
низький рівень гомології з ізоформою S6K2. Методи. Гібридомна технологія, ІФА, Вестерн-блот, імунопреципітація. Результати. Створено тригібридомних клони (A1, A2 і A3), які продукують моноклональні антитіла, специфічні до кінази S6K1. Висновки. Одержані моноклональні антитіла за своїми характеристикам можна використовувати для дослідження S6K1-залежних
сигнальних шляхів.
Ключові слова: кіназа рибосомного білка S6, МкАТ. Цель. Получить моноклональные антитела против N-концевого регуляторного участка киназы рибосомного белка S6 – S6K1, имеющего низкий уровень гомологии с S6K2 изоформой. Методы. Гибридомная технология, ИФА, Вестерн-блот, иммунопреципитация. Результаты. Созданы три гибридомных клона (A1, A2 и A3), продуцирующих моноклональные антитела, специфичные к киназе S6K1. Специфичность антител подтверждена методами Вестерн блота и иммунопреципитации. Выводы. Полученные моноклональные антитела по своим характеристикам можно использовать для изучения S6K1-зависимых сигнальных путей. Ключевые слова: киназа рибосомного белка S6, МкАТ.